2012
DOI: 10.1590/s1980-57642012dn06040010
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and quality of life assessment in patients with Parkinson's disease submitted to bilateral deep brain stimulation in the subthalamic nucleus

Abstract: Deep brain stimulation (DBS) has been widely used to control motor symptoms and improve quality of life in patients with Parkinsons disease (PD). Recently, DBS in the subthalamic nucleus (STN) has become the preferred target for patients with mixed motor symptoms. Despite resultant motor and quality of life improvements, the procedure has been associated with cognitive decline, mainly in language skills, and also with psychiatric symptoms.ObjectiveTo evaluate the influence of DBS in the STN on cognition, mood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…DBS patients exhibited deteriorations after surgery compared to preoperative performances in tasks of verbal fluency (5977), memory (59, 62, 64, 6668, 71, 72, 75, 77), executive function (59, 60, 64, 67, 69, 71, 72, 7680), attention (66, 71), visuospatial functioning (59, 72, 75), global cognition (62, 74, 78), abstract reasoning (62), and processing speed (64, 72, 76, 77). A few studies observed no cognitive changes up to 3 months (81), in which individuals who did decline were significantly older, had higher levels of levodopa at baseline, and all had left implants in the GPi, up to 6 months (82, 83), and up to 5 years (84), in which there was a trend for a decline in verbal fluency. Within other studies, the outcomes of verbal fluency were variable.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…DBS patients exhibited deteriorations after surgery compared to preoperative performances in tasks of verbal fluency (5977), memory (59, 62, 64, 6668, 71, 72, 75, 77), executive function (59, 60, 64, 67, 69, 71, 72, 7680), attention (66, 71), visuospatial functioning (59, 72, 75), global cognition (62, 74, 78), abstract reasoning (62), and processing speed (64, 72, 76, 77). A few studies observed no cognitive changes up to 3 months (81), in which individuals who did decline were significantly older, had higher levels of levodopa at baseline, and all had left implants in the GPi, up to 6 months (82, 83), and up to 5 years (84), in which there was a trend for a decline in verbal fluency. Within other studies, the outcomes of verbal fluency were variable.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…7 Targeting the STN significantly improves mobility, activities of daily life, and quality of life. 8,9 Placement of the DBS electrode is of importance for determining therapeutic effects since the STN has three parts, which form loops for somatosensory, associative, and limbic functions. In a single center study, one hundred and three patients with severe PD received bilateral STN stimulation and were followed up after 1 year.…”
Section: Dbs Of the Subthalamic Nucleus Targets Motor Complications I...mentioning
confidence: 99%
“…The subthalamic nucleus (STN) is the most popular target for DBS in PD 7 . Targeting the STN significantly improves mobility, activities of daily life, and quality of life 8,9 . Placement of the DBS electrode is of importance for determining therapeutic effects since the STN has three parts, which form loops for somatosensory, associative, and limbic functions.…”
Section: Dbs Of the Subthalamic Nucleus Targets Motor Complications I...mentioning
confidence: 99%